Paracaryum lalezarense (Boraginaceae), a new species from high alpine elevations of Lalezar Mountains, in Iran - Doostmohammadi, Moslem; Mirtadzadini, Mansour (Phytotaxa, 2019)
Paracaryum lalezarense is described as a new species endemic to the Lalezar Mountains in southeastern Iran. The new species is characterized by its moderately incurved nutlet wings, glochidiate nutlet wing margins, smooth and shiny nutlet disks and rather small flowers (corolla 3.5–4 mm long) with corolla tube as long as limb. It is restricted to high alpine and nival elevations (4,000–4,260 m) that is an infrequent phenomenon amongst other species of the genus Paracaryum. Description, photographs of living plants and distribution map of the new species are provided and taxonomic relationships with its closest possible allied species and its conservation status are briefly discussed.